2021
DOI: 10.3389/fcell.2021.632882
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of an Efficient Primary Culture System for Human Hair Follicle Stem Cells Using the Rho-Associated Protein Kinase Inhibitor Y-27632

Abstract: BackgroundHair follicle tissue engineering is a promising strategy for treating hair loss. Human hair follicle stem cells (hHFSCs), which play a key role in the hair cycle, have potential applications in regenerative medicine. However, previous studies did not achieve efficient hHFSC expansion in vitro using feeder cells. Therefore, there is a need to develop an efficient primary culture system for the expansion and maintenance of hHFSCs.MethodsThe hHFSCs were obtained by two-step proteolytic digestion combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…However, the exact mechanism by which Y-27632 induces the immortalization of keratinocytes remains elusive so far. Recently, one study suggested that Y-27632 maintained the proliferative capacity and stemness of human hair follicle stem cells through regulating the ERK/MAPK signaling pathway [45]. By contrast, another study also reported that the inhibition of PAK1-ROCK-Myosin II and TGF-β signaling pathways were crucial for the long-term proliferation of epithelial stem cells in a lowcalcium medium [46].…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact mechanism by which Y-27632 induces the immortalization of keratinocytes remains elusive so far. Recently, one study suggested that Y-27632 maintained the proliferative capacity and stemness of human hair follicle stem cells through regulating the ERK/MAPK signaling pathway [45]. By contrast, another study also reported that the inhibition of PAK1-ROCK-Myosin II and TGF-β signaling pathways were crucial for the long-term proliferation of epithelial stem cells in a lowcalcium medium [46].…”
Section: Discussionmentioning
confidence: 99%
“…The specific culture method used in this study provides a direction to develop HF tissue engineering and stem cell therapy for alopecia. 57 EpSlKCs exhibit a phenotypic profile that is similar to that of follicular keratinocytes and can crosstalk with DPCs to promote the proliferation of DPCs, thus facilitating HF morphogenesis in vivo. 62 Exosomes can transmit information between cells, and previous work has shown that dermal papilla cell-derived exosomes (DPC-Exos) extend the anagen stage, slow the catagen stage of the HC, and stimulate ORS cells to proliferate and differentiate.…”
Section: Hair Tissue Engineering and Regenerative Medicine For Alopeciamentioning
confidence: 99%
“…How to construct an efficient primary culture system for human HFSCs is a research focus 57 . Abreu et al showed that human interfollicular epidermal keratinocytes with stem‐like features (EpSlKCs) are ideal cells that can be used for hair regeneration 58 . Some specific microRNAs and dermal papilla cell‐derived exosomes (DPC‐Exos) could be potential therapeutic targets of HFSCs in hair loss 59‐61 …”
Section: The Significance Of Hfsc Behaviour In Alopeciamentioning
confidence: 99%
“…They identified that FOXA2 in ORS cells functions in regulating the trichogenicity of human ORS cells. Wen et al revealed that inhibition of Rho-Associated Protein Kinase by a specific inhibitor Y-27632 can increase the adhesion, proliferation, and stemness of the primary cultured human hair follicle stem cells through the ERK/MAPK pathway ( Wen et al, 2021 ). As two-dimensional (2D) cultured cells quickly lose their regenerative ability, most researches turned to modulate hair regeneration under 3D culture conditions.…”
Section: Hair Follicle Stem Cell Regeneration In Agingmentioning
confidence: 99%